Pengaruh Brand Ambassador Dan Kualitas Produk Terhadap Minat Beli Konsumen Pada Produk Avoskin : Studi Pada Mahasiswa Politeknik Negeri Malang Jurusan Administrasi Niaga Program Studi D-IV Manajamen Pemasaran - Bahari, Abigail Ellaura Fe; Afandi, Yosi (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
In the era following the Covid-19 pandemic, many beauty clinic consumers switched to using beauty products, especially skincare. With the increasing development of the skincare industry from year to year, various skincare brands have been emerging in Indonesia. Skincare companies can use brand ambassadors and product quality to create buying interest. This research analyzed the influence of brand ambassadors and product quality on Avoskin products partially and simultaneously on consumer buying interest. This research was quantitative and included explanatory research. The data collection technique was done by distributing questionnaires to 100 respondents who knew or had used Avoskin skincare products. The respondents were selected with the purposive sampling method. The data analysis method used multiple linear regression analysis and hypothesis testing. This study showed that brand ambassadorship and product quality have a positive and significant effect, both partially and simultaneously, on the interest in purchasing Avoskin skincare products. Based on the results of this research, it is recommended that Avoskin increase consumer trust in the existing brand ambassadors and maintain product quality through the ingredients provided. Therefore, Avoskin can create a sense of buying interest in consumers